ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI ADOPSI CLOUD ACCOUNTING PADA UMKM DI KOTA MATARAM - Bintang Olvi Syawila; Adhitya Bayu Suryantara (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the factors influencing cloud accounting adoption among Micro, Small, and Medium Enterprises (MSMEs) in Mataram City using the Technology–Organization–Environment (TOE) framework, specifically the factors of relative advantage, compatibility, competitor pressure, and business control. The research method used is a descriptive quantitative method with data collection through questionnaires to 85 MSMEs in Mataram City who have used cloud accounting applications for at least one year, using a purposive sampling technique. The results show that cloud accounting adoption among MSMEs in Mataram City has a positive impact on technological, organizational, and environmental aspects, where relative advantage and compatibility are the most dominant factors in driving adoption, characterized by increased efficiency, productivity, ease of financial management, and suitability of features to business needs. In addition, business control and competitor pressure also have a positive contribution in improving internal control, financial data quality, and MSME competitiveness, although their influence is not as strong as technological factors. The conclusion of this study is that the adoption of cloud accounting in MSMEs in Mataram City is significantly influenced by the perception of benefits and suitability of technology, so that increasing digital literacy and providing cloud accounting solutions that suit the characteristics of MSMEs are important factors in encouraging wider adoption. Keywords: Cloud Accounting, Relative Advantage, Compatibility, Competitor Pressure, Business Control, TOE Framewor